A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material

By introducing active six boron -boron powder and polyamide solutions in power battery heating membrane insulation materials, combined with the reaction between aldehyde and amino groups to prepare high -wear -resistant anti -scratching high -intensity heating membrane insulation composite materials, solving the power Difficulties in the use of batteries in low temperature environments have achieved higher thermal conductivity and high temperature resistance.

CN118755121BActive Publication Date: 2025-01-28GUANGDONG ZHONGYU HENGTONG ELECTRIC HEATING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410978589.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-28
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Power batteries are difficult to use in low temperature environments and seriously affect the service life and battery life of the battery pack, and require effective thermal management measures.

Method used

Using high-wear-resistant anti-scratching high-intensity heating film insulation composite material, this material combines six boronized pink powder with aldehydes silicane puppets and 2-amino-1,3,5-triazine and other compounds. The aminedehyde contraction reaction between the base and the amino group is prepared to obtain the active hexaponic boron mellastin powder, and mixes with the polyamine solution. Sexual heating membrane insulation composite material.

Benefits of technology

This composite material has higher wear resistance, heat resistance, and thermal conductivity. It can be used as a protective film and heating film of the battery, which significantly improves the performance of power batteries in low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004955337020000061
    Figure BDA0004955337020000061
  • Figure BDA0004955337020000071
    Figure BDA0004955337020000071
Patent Text Reader

Abstract

The present invention relates to a high wear-resistant and scratch-resistant high-strength heating film insulation composite material, and the preparation method includes: step 1, preparing aldehyde-formylation neodymium hexaboride powder; step 2, mixing aldehyde-formylation neodymium hexaboride powder and 2-amino-1,3,5-triazine in a first organic solvent, adding a first catalyst, stirring and reacting under the protection of nitrogen, and obtaining active neodymium hexaboride powder; step 3, preparing polyamic acid solution; step 4, mixing active neodymium hexaboride powder and polyamic acid solution to obtain a pre-reaction liquid; step 5, adding a second catalyst and a dehydrating agent into the pre-reaction liquid, after casting, sequentially undergoing drying treatment and thermal cyclization treatment to obtain a heating film insulation composite material. The composite material prepared by the present invention has higher wear resistance and scratch resistance, heat resistance and thermal conductivity compared to traditional polyimide materials, and can be used as a protective film and a heating film of a battery at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery materials, and in particular to a high-wear-resistant, scratch-resistant and high-strength heating film insulation composite material. Background Art

[0002] Power batteries are batteries used in new energy vehicles, and their stable operation as energy sources is critical. The direct impact of batteries on electric vehicles has also made major new energy manufacturers and battery suppliers rack their brains to promote methods to increase battery life. However, whether it is a physical battery stack solution, or a method of changing the composition elements of the battery electrolyte, or even changing the form of matter, in the face of low temperatures, the battery life of these batteries cannot even present a normal state. How to keep the battery warm and warm at low temperatures has become the key to fighting this "battery killer". In a low temperature environment, the activity of the positive and negative electrode materials of the battery decreases, and the conductivity of the electrolyte that acts as a bridge also decreases. Therefore, when the battery is charged and discharged, resistance will be generated inside, which is called internal resistance. When the internal resistance of the battery increases, a large amount of Joule heat will be generated during the normal use of the battery, causing the battery temperature to rise. Experiments show that when the environment is below 0°C, the internal resistance increases by about 15% for every 10°C drop in temperature. The battery is difficult to start and use at low temperatures, and it seriously affects the service life and battery life of the battery pack. Therefore, the power lithium battery pack must be effectively thermally managed, and heating treatment is required when used in a low temperature environment.

[0003] With the application of various advanced technologies in energy density, the importance of safety and cost of use in power batteries has become increasingly prominent. Heating film has become the mainstream in battery heating methods due to its outstanding cost-effectiveness. Because there are multiple welding processes in each production link of power batteries and the assembly conditions are relatively complex, in order to ensure the safety of the heating film, a high-strength heating film insulation material with high wear resistance and scratch resistance is required. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material, and a preparation method thereof, comprising:

[0007] Step 1, putting neodymium hexaboride powder and aldehyde silane coupling agent into anhydrous ethanol, mixing and stirring, heating, and then filtering, washing and drying in sequence to prepare aldehyde-treated neodymium hexaboride powder;

[0008] Step 2, mixing the aldehyded neodymium hexaboride powder and 2-amino-1,3,5-triazine in a first organic solvent, stirring and reacting under the action of a catalyst, and then filtering, washing and drying in sequence to obtain active neodymium hexaboride powder;

[0009] Step 3, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in a second organic solvent, stirring until uniform, to obtain a polyamic acid solution;

[0010] Step 4, mixing the active neodymium hexaboride powder and the polyamic acid solution, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution;

[0011] Step 5, adding a catalyst and a dehydrating agent into the pre-reaction liquid, stirring it sufficiently, degassing it and transferring it to a casting machine, and after casting, sequentially undergoing drying treatment and thermal cyclization treatment to obtain a heating film insulating composite material.

[0012] Preferably, in step 1, the purity of the neodymium hexaboride powder is higher than 99%, and the particle size is 100±10 μm; and the aldehyde silane coupling agent is 4-(triethoxysilyl)butyraldehyde.

[0013] Preferably, in step 1, the mass volume ratio of neodymium hexaboride powder, aldehyde silane coupling agent and anhydrous ethanol is 1 g: (0.23-0.46) g: (10-20) mL.

[0014] Preferably, in step 1, the temperature is 65-85° C., the stirring time is 6-12 h, and the stirring speed is 200-300 r / min.

[0015] Preferably, in step 2, the first organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0016] Preferably, in step 2, the mass volume ratio of the formaldehyded neodymium hexaboride powder, 2-amino-1,3,5-triazine and the first organic solvent is 1 g:(0.32-0.64) g:(10-20) mL.

[0017] Preferably, in step 2, the catalyst is anhydrous acetic acid, and the added amount is 3%-7% of the mass of 2-amino-1,3,5-triazine.

[0018] Preferably, in step 2, the reaction needs to be carried out under the protection of nitrogen, the reaction temperature is 80-100° C., the reaction time is 4-8 h, and the stirring speed is 200-300 r / min.

[0019] Preferably, in step 3, the second organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0020] Preferably, in step 3, the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and the second organic solvent is (0.21-0.42) g: (0.36-0.72) g: (10-20) mL.

[0021] Preferably, in step 3, the stirring temperature is room temperature, the stirring time is 0.5-1h, and the stirring speed is 200-300r / min.

[0022] Preferably, in step 4, the mass volume ratio of the active neodymium hexaboride powder to the polyamic acid solution is (1.2-2.4) g: (10-20) mL.

[0023] Preferably, in step 5, the catalyst is quinoline, and the amount added is 15%-25% of the mass of the pre-reaction liquid; the dehydrating agent is acetic anhydride, and the amount added is 15%-25% of the mass of the pre-reaction liquid.

[0024] Preferably, in step 5, the temperature of the drying treatment is 110-130° C. and the time is 1-2 h; the temperature of the thermal cyclization treatment is 200-250° C. and the time is 4-6 h.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention provides a highly wear-resistant, scratch-resistant, high-strength heating film insulation composite material, which can be used for the preparation of power battery heating films. The present invention uses active neodymium hexaboride powder as a reinforcing modifier on the basis of polyimide materials to prepare a composite material. Compared with traditional polyimide materials, the composite material prepared by the present invention has higher wear resistance, scratch resistance, heat resistance and thermal conductivity, and can be used as a protective film and heating film for batteries at the same time.

[0027] 2. Polyimide PI film is a commonly used material for power battery protection. It has excellent mechanical properties and high temperature resistance. However, due to its relatively low thermal conductivity, it is less effective as a heating film. In addition, due to the characteristics of polyimide, it has poor compatibility with other materials. Adding thermal conductive fillers often results in poor compatibility, resulting in a decrease in the overall performance of the protective film. In view of this, the present invention adds active neodymium hexaboride powder during the synthesis of polyimide, which not only has good compatibility and greatly improves the thermal conductivity of the material, but also the resulting composite material has higher strength, better wear resistance and better high temperature resistance.

[0028] 3. The active neodymium hexaboride powder prepared by the present invention is based on neodymium hexaboride powder with good thermal conductivity and poor electrical conductivity. After the surface treatment of aldehyde group, it is combined with the triazine compound 2-amino-1,3,5-triazine containing amino group, and the amine-aldehyde condensation reaction between the aldehyde group and the amino group is performed to obtain a composite powder with organic matter coated on the surface. The active neodymium hexaboride powder obtained by the treatment of the present invention is applied to polyimide materials, and not only has good dispersibility, but also has better performance, which may be related to the rich triazine, Schiff base and other groups on its surface.

[0029] 4. In the process of preparing the insulating composite material of the present invention, the added catalyst quinoline is a low-temperature curing catalyst, which can reduce the subsequent heat treatment cyclization temperature of the polyimide to 200-250°C. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0031] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0032] The present invention will be further described below in conjunction with the following examples.

[0033] Example 1

[0034] A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material, and a preparation method thereof, comprising:

[0035] Step 1, putting neodymium hexaboride powder (purity higher than 99%, particle size of 100±10μm) and 4-(triethoxysilyl)butyraldehyde into anhydrous ethanol, the mass volume ratio of neodymium hexaboride powder, 4-(triethoxysilyl)butyraldehyde and anhydrous ethanol is 1g:0.36g:15mL, mixing and stirring evenly, reflux stirring at 75°C for 10h, stirring speed of 300r / min, after the reaction is completed, filtering and collecting the residue, washing with alcohol three times, and drying under reduced pressure to prepare aldehyded neodymium hexaboride powder;

[0036] Step 2, mixing the aldehyded neodymium hexaboride powder and 2-amino-1,3,5-triazine in N-methylpyrrolidone, the mass volume ratio of the aldehyded neodymium hexaboride powder, 2-amino-1,3,5-triazine and N-methylpyrrolidone is 1g:0.48g:15mL, introducing nitrogen as a protective gas, stirring and reacting under the catalytic action of anhydrous acetic acid, the amount of anhydrous acetic acid added is 5% of the mass of 2-amino-1,3,5-triazine, the reaction temperature is 90°C, the reaction time is 6h, the stirring speed is 250r / min, after the reaction is completed, filtering and collecting the filter residue, washing with alcohol three times, and drying under reduced pressure to obtain active neodymium hexaboride powder;

[0037] Step 3, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in N,N-dimethylformamide, the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide is 0.31g:0.54g:15mL, stirring at room temperature for 0.6h, and the stirring speed is 250r / min to obtain a polyamic acid solution;

[0038] Step 4, mixing the active neodymium hexaboride powder and the polyamic acid solution, the mass volume ratio of the active neodymium hexaboride powder and the polyamic acid solution is 1.8 g:15 mL, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution;

[0039] Step 5, add quinoline as a catalyst to the pre-reaction liquid in an amount of 20% of the mass of the pre-reaction liquid, then add acetic anhydride as a dehydrating agent in an amount of 20% of the mass of the pre-reaction liquid, stir thoroughly, degas and transfer to a casting machine, after casting, dry at 120°C for 1.5h, then heat to 225°C for 5h, after the cyclization treatment is completed, a heating film insulating composite material is obtained.

[0040] Example 2

[0041] A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material, and a preparation method thereof, comprising:

[0042] Step 1, putting neodymium hexaboride powder (purity higher than 99%, particle size of 100±10μm) and 4-(triethoxysilyl)butyraldehyde into anhydrous ethanol, the mass volume ratio of neodymium hexaboride powder, 4-(triethoxysilyl)butyraldehyde and anhydrous ethanol is 1g:0.23g:10mL, mixing and stirring evenly, reflux stirring at 65°C for 6h, and the stirring speed is 200r / min. After the reaction is completed, filtering and collecting the filter residue, washing with alcohol three times, and drying under reduced pressure to prepare aldehyded neodymium hexaboride powder;

[0043] Step 2, mixing the aldehyded neodymium hexaboride powder and 2-amino-1,3,5-triazine in N,N-dimethylformamide, the mass volume ratio of the aldehyded neodymium hexaboride powder, 2-amino-1,3,5-triazine and N,N-dimethylformamide is 1g:0.32g:10mL, introducing nitrogen as a protective gas, stirring and reacting under the catalytic action of anhydrous acetic acid, the amount of anhydrous acetic acid added is 3% of the mass of 2-amino-1,3,5-triazine, the reaction temperature is 80°C, the reaction time is 4h, the stirring speed is 200r / min, after the reaction is completed, filtering and collecting the filter residue, washing with alcohol three times, and drying under reduced pressure to obtain active neodymium hexaboride powder;

[0044] Step 3, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in N,N-dimethylformamide, the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide is 0.21g:0.36g:10mL, stirring at room temperature for 0.5-1h, and the stirring speed is 200r / min to obtain a polyamic acid solution;

[0045] Step 4, mixing the active neodymium hexaboride powder and the polyamic acid solution, the mass volume ratio of the active neodymium hexaboride powder and the polyamic acid solution is 1.2 g:10 mL, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution;

[0046] Step 5, add quinoline as a catalyst to the pre-reaction liquid in an amount of 15% of the mass of the pre-reaction liquid, then add acetic anhydride as a dehydrating agent in an amount of 15% of the mass of the pre-reaction liquid, stir thoroughly, degas and transfer to a casting machine, after casting, dry at 110°C for 1h, then heat to 200°C for 6h, after the cyclization treatment is completed, a heating film insulating composite material is obtained.

[0047] Example 3

[0048] A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material, and a preparation method thereof, comprising:

[0049] Step 1, putting neodymium hexaboride powder (purity higher than 99%, particle size of 100±10μm) and 4-(triethoxysilyl)butyraldehyde into anhydrous ethanol, the mass volume ratio of neodymium hexaboride powder, 4-(triethoxysilyl)butyraldehyde and anhydrous ethanol is 1g:0.46g:20mL, mixing and stirring evenly, reflux stirring at 85°C for 12h, stirring speed of 300r / min, after the reaction is completed, filtering and collecting the residue, washing with alcohol three times, and drying under reduced pressure to prepare aldehyded neodymium hexaboride powder;

[0050] Step 2, mixing the aldehyded neodymium hexaboride powder and 2-amino-1,3,5-triazine in N-methylpyrrolidone, the mass volume ratio of the aldehyded neodymium hexaboride powder, 2-amino-1,3,5-triazine and N-methylpyrrolidone is 1g:0.64g:20mL, introducing nitrogen as a protective gas, stirring and reacting under the catalytic action of anhydrous acetic acid, the amount of anhydrous acetic acid added is 7% of the mass of 2-amino-1,3,5-triazine, the reaction temperature is 100°C, the reaction time is 8h, the stirring speed is 300r / min, after the reaction is completed, filtering and collecting the filter residue, washing with alcohol three times, and drying under reduced pressure to obtain active neodymium hexaboride powder;

[0051] Step 3, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in N-methylpyrrolidone, the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N-methylpyrrolidone is 0.42g:0.72g:20mL, stirring at room temperature for 1h, and the stirring speed is 300r / min to obtain a polyamic acid solution;

[0052] Step 4, mixing the active neodymium hexaboride powder and the polyamic acid solution, the mass volume ratio of the active neodymium hexaboride powder and the polyamic acid solution is 2.4g:20mL, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution;

[0053] Step 5, adding quinoline as a catalyst to the pre-reaction liquid in an amount of 15%-25% of the mass of the pre-reaction liquid, and then adding acetic anhydride as a dehydrating agent in an amount of 25% of the mass of the pre-reaction liquid. After sufficient stirring, degassing and transferring to a casting machine, after casting, drying at 130°C for 2h, and then heating to 250°C for 4h. After the cyclization treatment is completed, a heating film insulating composite material is obtained.

[0054] Comparative Example 1

[0055] A heating film insulating composite material, the preparation method of which is different from that of Example 1 in that the active neodymium hexaboride powder is replaced with neodymium hexaboride powder; namely:

[0056] Step 1, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in N,N-dimethylformamide, the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide is 0.31g:0.54g:15mL, stirring at room temperature for 0.6h, and the stirring speed is 250r / min to obtain a polyamic acid solution;

[0057] Step 2, mixing the neodymium hexaboride powder and the polyamic acid solution, the mass volume ratio of the neodymium hexaboride powder and the polyamic acid solution is 1.8g:15mL, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution;

[0058] Step 3, add quinoline as a catalyst to the pre-reaction liquid in an amount of 20% of the mass of the pre-reaction liquid, then add acetic anhydride as a dehydrating agent in an amount of 20% of the mass of the pre-reaction liquid, stir thoroughly, degas and transfer to a casting machine, after casting, dry at 120°C for 1.5h, then heat to 225°C for 5h, after the cyclization treatment is completed, a heating film insulating composite material is obtained.

[0059] Comparative Example 2

[0060] A heating film insulating composite material, the preparation method of which is different from that of Example 1 in that the active neodymium hexaboride powder is replaced with formaldehyde-treated neodymium hexaboride powder, and the remaining processes and proportions remain unchanged, with specific reference to Comparative Example 1.

[0061] Comparative Example 3

[0062] A heating film insulating composite material, whose preparation method is different from that of Example 1 in that the active neodymium hexaboride powder is replaced by a mixture of neodymium hexaboride powder and 4,4'-diaminodiphenyl ether, the mass ratio of neodymium hexaboride powder to 4,4'-diaminodiphenyl ether is 1:0.48, and the remaining processes and proportions remain unchanged, please refer to Comparative Example 1 for details.

[0063] Experimental testing

[0064] The properties of the heating film insulating composite materials of the heating films prepared in Example 1 and Comparative Examples 1-3 were tested accordingly, and the test items included tensile strength, elongation at break, friction coefficient, electrical strength, heat deformation temperature and thermal conductivity.

[0065] The testing standards for tensile strength and elongation at break refer to GB / T 1040-2006, the testing standards for electrical strength refer to GB / T1408.1-2016, the testing standards for friction coefficient refer to GB / T 10006-1988, the testing standards for heat deformation temperature refer to GB / T1634.1-2004, and the testing standards for thermal conductivity refer to GB / T 3399-1982.

[0066] The test results are shown in Table 1:

[0067] Table 1 Test results of different heating film insulation composite materials

[0068]

[0069]

[0070] It can be seen from Table 1 that compared with Comparative Examples 1-3, the heating film insulation composite material prepared in Example 1 of the present invention has the best comprehensive performance. The tensile strength and elongation at break are higher, indicating that it has high mechanical strength; the friction coefficient is lower, indicating that it has better wear resistance and scratch resistance; the electrical strength is higher, indicating that it has better insulation; the thermal conductivity is higher and the heat deformation temperature is high, indicating that it has better thermal conductivity and high temperature resistance. In summary, it is shown that the heating film insulation composite material prepared in Example 1 of the present invention has higher strength, better wear resistance and more excellent heat resistance performance.

[0071] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0072] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material, characterized in that: The preparation method of the heating film insulation composite material comprises: Step 1, putting the neodymium hexaboride powder and the aldehyde silane coupling agent into anhydrous ethanol, heating to 65-85° C., reflux stirring for 6-12 hours, and then filtering, washing and drying in sequence to obtain the aldehyde-treated neodymium hexaboride powder; Step 2, mixing the aldehyded neodymium hexaboride powder and 2-amino-1,3,5-triazine in a first organic solvent, adding a first catalyst, stirring and reacting under the protection of nitrogen, the reaction temperature is 80-100° C., the reaction time is 4-8 hours, and after the reaction is completed, filtering, washing and drying are performed in sequence to obtain active neodymium hexaboride powder; Step 3, mixing pyromellitic anhydride and 4,4'-diaminodiphenyl ether in a second organic solvent, and stirring at room temperature for 0.5-1h to obtain a polyamic acid solution; Step 4, mixing the active neodymium hexaboride powder and the polyamic acid solution, and continuing to stir at room temperature until the mixture is uniformly mixed to obtain a pre-reaction solution; Step 5, adding the second catalyst and the dehydrating agent into the pre-reaction liquid, stirring sufficiently, degassing and transferring to a casting machine, and after casting, sequentially undergoing drying treatment and thermal cyclization treatment to obtain a heating film insulating composite material.

2. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In the step 1, the purity of the neodymium hexaboride powder is higher than 99%, and the particle size is 100±10 μm; the aldehyde silane coupling agent is 4-(triethoxysilyl)butyraldehyde.

3. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In the step 1, the mass volume ratio of the neodymium hexaboride powder, the aldehyde silane coupling agent and the anhydrous ethanol is 1 g: (0.23-0.46) g: (10-20) mL.

4. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In the step 2, the first organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

5. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In the step 2, the mass volume ratio of the formaldehyded neodymium hexaboride powder, 2-amino-1,3,5-triazine and the first organic solvent is 1 g: (0.32-0.64) g: (10-20) mL.

6. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In the step 2, the first catalyst is anhydrous acetic acid, and the added amount is 3%-7% of the mass of 2-amino-1,3,5-triazine.

7. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In step 3, the second organic solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; the mass volume ratio of pyromellitic anhydride, 4,4'-diaminodiphenyl ether and the second organic solvent is (0.21-0.42) g:(0.36-0.72) g:(10-20) mL.

8. The high wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In step 4, the mass volume ratio of the active neodymium hexaboride powder and the polyamic acid solution is (1.2-2.4) g: (10-20) mL.

9. The highly wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In step 5, the second catalyst is quinoline, and the added amount is 15%-25% of the mass of the pre-reaction liquid; the dehydrating agent is acetic anhydride, and the added amount is 15%-25% of the mass of the pre-reaction liquid.

10. The high wear-resistant, scratch-resistant and high-strength heating film insulation composite material according to claim 1, characterized in that: In step 5, the drying treatment temperature is 110-130° C. and the time is 1-2 h; the thermal cyclization treatment temperature is 200-250° C. and the time is 4-6 h.

Citation Information

Patent Citations

  • Preparation method for wear-resistant polyurea coating based on organic-inorganic dual modification treatment

    CN108047904A

  • High-temperature-resistant neodymium-iron-boron magnet and preparation method thereof

    CN111696743A